NILAI-NILAI PENDIDIKAN ISLAM DALAM BUDAYA LOKAL DI KAMPUNG AL-MUNAWAR PALEMBANG - Ratna Juita; Abu Mansur; Irja Putra Pratama; Alimron Alimron (PAI RAFAH, 2020)
Local culture is a culture that has become the hallmark of a society that can distinguish it from locality or region with one region or another place. One of the local cultures in Al-Munawar village is haul, haul is a culture of the commemoration of the death of the founder of Al-Munawar village which coincided with Isra ’Mi'raj which contained various Islamic nuanced activities. Based on the description above, the main problem in this study is: what are the values of Islamic education in local culture, namely the culture of haul in Al-Munawar village, Palembang? The purpose of this study is to explain the historical background of haul culture in Palembang's Al-Munawar village, the process of the haul culture, and what Islamic education values are contained in haul culture in Palembang's Al-Munawar village. This type of research is a qualitative research with a descriptive approach. Data collection techniques using observation, in-depth interviews and documentation, data analysis is qualitative analytic, the data analysis method starts from the stage of data reduction, data presentation, triangulation and verification. Based on the results of research conducted by researchers in Al-Munawar 13 Ulu Palembang village, it can be concluded that the background of the implementation of haul is the desires of Al-Munawar descendants to remember the history of Al-Munawar village, the story of the founder of the village, namely habib Abdurrahman bin Muhammad Al-Munawar was a scholar from Yemen who initially preached while trading. The process of implementing this haul culture includes: reading of burdah, pilgrimage, prayer, tasyakuran or aqiqah, marriage contract, reading of yasin and tahlil, tausiyah, zuhr prayer in congregation for men and lunch kebuli rice. The values of Islamic education in this haul culture include: historical values, religious values include; remembering death, friendship, the assembly of knowledge, alms, and moral values.